1998
DOI: 10.1071/rd98096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the merits of measuring equine chorionic gonadotrophin (eCG) and blood and faecal concentrations of oestrone sulphate for determining the pregnancy status of miniature horses

Abstract: The relative merits of measuring blood concentrations of equine chorionic gonadotrophin (eCG, previously known as pregnant mare serum gonadotrophin (PMSG)), or oestrone sulphate (OS), or faecal OS concentrations for determining pregnancy status in miniature horses were investigated. Pregnant mares between 40 and 140 days after mating had serum eCG concentrations > 1 I.U. mL-1, with the highest concentrations occurring between days 50 and 120. However, eCG measurements were susceptible to returning a 'false pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…-16 week of pregnancy. It is in agreement with previous studies: only in miniature horses Henderson et al (1998) suggested that the foeto-placental unit can synthesize eostrogens in earlier (then week 15) stages of pregnancy. Hoffmann et al (1996) have found an increase in conjugated oestrogens level between week 5 and 10 of pregnancy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…-16 week of pregnancy. It is in agreement with previous studies: only in miniature horses Henderson et al (1998) suggested that the foeto-placental unit can synthesize eostrogens in earlier (then week 15) stages of pregnancy. Hoffmann et al (1996) have found an increase in conjugated oestrogens level between week 5 and 10 of pregnancy.…”
Section: Discussionsupporting
confidence: 94%
“…This discrepancy is likely due to the different timing of oestrogen secretion into the blood in comparison to its excretion via faeces. Numerous reports showed that an initial increase of oestrogens in the blood is then followed by its elevation in faeces (Schwarzenberg et al, 1996;Henderson et al, 1998). From these relationships it can be concluded that faecal oestrogen concentration does not allow to control of the embryonic death in mares.…”
Section: Discussionmentioning
confidence: 99%
“…Daily total urinary oestrogen excretion, estimated using the Kober reaction, peaked at around 400-800 mg/24 h [25]. Since then, methods for measuring estrone sulphate in peripheral blood of mares, most aimed at validating a test for pregnancy, have utilised immunoassays of various types, direct and otherwise, [8,[10][11][12]14,15,22,46,47]. Again, the estimates of peak concentrations (without deconjugation or separation of constituent estrogens) by immunoassay, about 1 lg/mL, are difficult to relate to those reported in the earlier studies though the pattern of secretion is consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many oestrogens secreted and excreted in urine during equine pregnancy, estrone sulphate is present in the highest concentrations at approximately 50% of the conjugates [9]. The analysis of serum or plasma concentrations of conjugated oestrogens by radio-immunoassay, has allowed for the development of an early (after days 60-70) detection pregnancy test for horses [10][11][12][13][14][15]. Perhaps because of the focus on early pregnancy diagnosis as a potential clinical application, surprisingly few studies have examined estrone sulphate concentrations throughout equine pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%